Adolescent Social Networks and Physical, Verbal, and Indirect Aggression in China: The Moderating Role of Gender - Zhang, Maoxin; Liu, Hongyun; Zhang, Yunyun (Frontiers in Psychology, 2020)
Aggressive adolescents are preferable in some Western cultures, whereas Confucianism places great emphasis on the inhibition of aggressive behaviors in Chinese culture. Using the longitudinal social network analysis, we used a sample of 1354 Chinese adolescents (54% boys, ages 12–15) who were followed over 1 year at three time points to examine the association between friendship dynamics and physical, verbal, and indirect aggression and the moderating role of gender. This study found the following: (1) Students who were verbally aggressive were regarded as attractive, whereas those who were indirectly aggressive were unattractive as friends; (2) adolescents selected peers with similar levels of aggression as friends; (3) adolescents were influenced by their friends’ aggressive behaviors; and (4) girls were more susceptible than boys to the influence of physical aggression, although gender did not moderate the influence process of verbal and indirect aggression. The findings of this study provided a clearer insight into the selection and influence processes of the three subtypes of aggression and contributed to the diversity of samples. Chinese educators should pay more attention to both verbal aggression because of youths’ preference for it and to girls with physically aggressive friends since they are more susceptible than boys.